2015 parliamentary elections in Turkey: demise and revival of AKP's single-party rule. (2nd January 2016) - Bardakçi, Mehmet
ABSTRACT: Turkey held two consecutive parliamentary elections in an interval of five months that produced entirely different results. The June 7 elections saw the Adalet ve Kalkınma Partisi (AKP) lose its parliamentary majority and the rise of the Halkların Demokratik Partisi (HDP) as a game-changer. Following the collapse of coalition talks, the subsequent snap elections held on November 1, 2015 took place under a dramatically different context, being marked with issues of security and stability that trumped the issues that were decisive in the June 7 elections, such as the economic slowdown, growing authoritarianism, and allegations of corruption. The electorate's search for a stable and strong government, the AKP's adjustments in an apparent response to the criticisms of the electorate, and the mistakes made by opposition parties gave the AKP the opportunity once again to form a single-party government after the November 1 elections.